Lactato sérico como factor pronóstico de mortalidad en pacientes adultos críticos con sepsis severa y shock séptico - Segura Franco, Carlos Antonio (2017)
Introduction: The production of lactate is a result of cellular processes and its increase is a consequence, among other causes, of hypo perfusion of the tissues. Regardless of the mechanism, it has been observed in several studies that increased serum lactate increased to the patients’ admission is associated with a worse prognosis and mortality. Objective: To determine the usefulness of serum lactate as a predictor of mortality in critically ill patients with severe sepsis and septic shock Materials and Methods: Cases and controls study. A total of 182 patients admitted to the ICU during the period 2011-2016 with a diagnosis of severe sepsis and septic shock were studied divided in 91 cases (deceased) and 91 controls (survivors). The value of serum lactate was determined and the odds ratio (OR) was found. The exposed group consisted of patients with lactate level (> = 2mmol / L).The ROC curve was determined for the maximum point of S and E. Results: We studied a total of98 women (53.8%) and 84 men (46.2%). The mean age of the cases compared to the controls was (62.4 vs 59.11 p = 0.0001). Mortality was 27.9% and 41.1% for severe sepsis and septic shock, respectively. There was a significant association between serum lactate at admission (> 2) and mortality in patients with an OR of 2.248 (95% CI, 1.238 - 4.082), with serum lactate> = 2.45 being the highest sensitivity and specificity for Predict mortality A lactate value> 2.45 mmol / L (OR 4.73) with an area under the curve (AUC) of 68% (95% CI, 0.601 – 0.758) was also determined to be p <0.001. Conclusion: Serum lactate elevated at admission (> = 2) is a predictive factor of mortality for critically ill patients with severe sepsis and septic shock